Synergistic effects of side-functionalization and aza-substitution on the charge transport and optical properties of perylene-based organic materials: a DFT study - Debata, Suryakanti; Khatua, Rudranarayan; Sahu, Sridhar (New journal of chemistry, 2022)
The physicochemical properties of organic materials are subject to the chemical structure of the molecular unit and the arrangement of molecules in a crystal. Herein, a series of perylene-based small-molecule organic semiconductors (OSCs) have been theoretically designed by subsequent functionalization of cyclic side chains and N-doping in perylene units. Different physicochemical properties of the designed molecules were explored using density functional theory. As a result of the synergistic effects of side-functionalization and aza-substitution in the parent perylene, a low-lying LUMO level (−3.926 eV) and high electron affinity (2.939 eV) have been achieved for the designed compound ( P16 ), which are favourable for air-stable electron injection. The molecular packing motif and high intermolecular electron coupling in the P16 crystal led to enhanced electron mobility up to 0.017 cm 2 V −1 s −1 , making it a promising air-stable n-channel OSC. In addition, these perylene derivatives are also found to be optically active in the UV-visible region, which further experiences a bathochromic shift after substituting all peri-positions with the cyclic-substituents. The present study is therefore aimed at designing novel n-type and optically active small-molecule OSCs, which will be beneficial for several organic electronic devices. The physicochemical properties of organic materials are subject to the chemical structure of the molecular unit and the arrangement of molecules in a crystal.